PLANNING OF RUNWAY PAVEMENT REHABILITATION USING THE PAVEMENT CONDITION INDEX (PCI) METHOD AT ATUNG BUNGSU AIRPORT, PAGAR ALAM, SOUTH SUMATRA - Wahyu Dwi Kusumo, Arya; Triyono, Agus; Purwayudhaningsari, Ranatika (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2025)
The airside facility of Atung Bungsu Pagar Alam Airport has a runway of 1500 meters and a width of 30 meters with a PCN of 24 F/C/X/T. Pagar Alam Atung Bungsu Airport currently has a problem, namely the presence of Loss Material that occurs on almost the entire runway surface. The purpose of this study was to analyze the condition of the runway pavement using the PCI (Pavement Condition Index) method. PCI is a runway pavement assessment system based on the type, level, and extent of damage that occurs, and can be used as a maintenance effort. In assessing the condition of the runway using the Pavement Condition Index (PCI) method, data on the characteristics of the runway and direct field conditions are used. The calculation is done by dividing the runway into several segments, namely every 100 m. Then, each segment is observed (visually) and measured to identify the type of damage that exists and conduct an assessment according to the PCI method. The results of this study indicate that the overall average value of the runway STA of Atung Bungsu Airport is 33.83 with a poor category. The maintenance program includes an overlay with a thickness of 5 cm and the need for routine and scheduled supervision at each STA so that the budget plan for the overlay cost is estimated at Rp. 14,066,667,092.16 (Fourteen Billion Sixty Million Six Hundred Sixty Seven Ninety Two Point Sixteen) based on the basic unit price of wages and construction materials of the Pagar Alam City Government in 2024 and PM 78 of 2014.